Reusable and efficient heterogeneous catalysts for biodiesel production from free fatty acids and oils: Self-solidifying hybrid ionic liquids. (15th November 2020) - Li, Mantian; Chen, Jinyi; Huang, Youjie; Li, Meichen; Lin, Xiaocheng; Qiu, Ting
Abstract: A series of self-solidifying hybrid ionic liquids (SHILs) were synthesised via a mild nucleophilic substitution reaction between (3-aminopropyl)trimethoxysilane and 1, 3-propanesultone followed by a facile sol-gel reaction, during which not any acid, catalyst or support was introduced. Part of the grafted –SO3 H groups would make SHILs become solid nature by forming the zwitterion, while the rest of –SO3 H groups could endue SHILs with acidic catalytic sites. Besides, –Si–O–Si– networks formed by the sol-gel reaction would further impart the water-tolerance and heterogeneity to SHILs, conducive to the easy separation and good reusability. For the oleic acid esterification catalysed by P-APTMS-PS-5 SHIL, 96.55% conversion was achieved under appropriate conditions (optimised by response surface methodology), and the catalytic activity well remained after 7 cycles. More importantly, SHILs exhibited excellent catalytic activity and satisfactory generality in the esterification of various free fatty acids, as well as in the transesterification of different oils, signifying the great potential for biodiesel production. Highlights: Acidic heterogeneous catalysts were synthesised for biodiesel production. The synthesis process was efficient, facile and mild. The catalysts have high catalytic activity and stability and ease of recovery. Extremely high free fatty acid conversion and re-use ability can be achieved.